Manajemen Emosi Pada Pasien Anak Rawat Inap (Hospitalized Children) Melalui Ekspresi Tulis & Gambar - Dian Sari Utami; Amitya Kumara (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2007)
Children are very vulnerable with their bodies, especially when they are ill. This condition is so uncomfortable for children to get ill, moreover when they have to be hospitalized. Children usually have chronic illness and should be hospitalized for long time. This condition would affect not only their bodies, but their minds and emotions. Hospitalized would make children getting stress or distress and need to cope. One way to cope is managing their emotions through writing and drawing as a method to express their emotions. This study used the book as a media to express their emotion called â€œPelangi Hatikuâ€.Â Â Â Â Â Â Â Â Â The qualitative method using in this study is case study. The participants who involved in this case study were 3 children of 8-12 years-old from 2 general hospitals in Yogyakarta. They were interviewed and observed regarding to their steps of managing emotions using â€œPelangi Hatikuâ€.Â Â Â Â Â Â Â Â Â It was found that managing emotions consisted of four steps, they are spontaneously, event thinking deeply, involving or withdrawal from emotions reflectively, reducing negative emotions by increasing positive emotions. Furthermore, the Emotional Detections Scale from pre test and post test showed the score decreasing in which means that there was increasing in their abilities to manage their emotions.Â KeywordsÂ Â Â Â : Â Â Â emotional management, writing, drawing